“Estabilización de plomo y zinc en las aguas del río Moche para aplicación edáfica en la Cuenca Alta – Moche – Trujillo – 2022 - Cabrera Martos, Lorena Esmeralda (2023)
The objective of this investigation was to evaluate the chemical chelation method for subsequent edaphic application using EDTA (ethylenediaminetetraacetic acid) and magnesium citrate as ligands in the waters of the Moche River in Trujillo - Peru, focused on the heavy metals lead and zinc. In which, it was determined that its concentration exceeds the values of the National Environmental Quality Standards (ECA) for Water established in Supreme Decree No. 004-2017-MINAM. The initial concentrations taken were 0.25 ppm for lead and 0.188 ppm for zinc, therefore, applying the chelating agents EDTA and Citrate, a lead chelation of 67.16% (0.0821 ppm) and 54.18% (0.1145 ppm) respectively was achieved; and for zinc a chelation of 33.10% (0.1258 ppm) and 29.48% (0.1326 ppm) respectively was achieved, in both cases a previous treatment was applied to the water samples of 300 ml of 0.1 N NaOH in solution for the elimination of ferric iron (Fe3+)